The Benefits of High-Intensity Interval Training on Cognition and Blood Pressure in Older Adults With Hypertension and Subjective Cognitive Decline: Results From the Heart & Mind Study - Boa Sorte Silva, Narlon C.; Petrella, Andrea F. M.; Christopher, Nathan; Marriott, Catherine F. S.; Gill, Dawn P.; Owen, Adrian M.; Petrella, Robert J. (Frontiers in Aging Neuroscience, 2021)
Background: The impact of exercise on cognition in older adults with hypertension and subjective cognitive decline (SCD) is unclear. Objectives: We determine the influence of high-intensity interval training (HIIT) combined with mind-motor training on cognition and systolic blood pressure (BP) in older adults with hypertension and SCD. Methods: We randomized 128 community-dwelling older adults (age mean [SD]: 71.1 [6.7], 47.7% females) with history of hypertension and SCD to either HIIT or a moderate-intensity continuous training (MCT) group. Both groups received 15 minutes of mind-motor training followed by 45 minutes of either HIIT or MCT. Participants exercised in total 60 minutes/day, 3 days/week for 6 months. We assessed changes in global cognitive functioning (GCF), Trail-Making Test (TMT), systolic and diastolic BP, and cardiorespiratory fitness. Results: Participants in both groups improved diastolic BP (F[1, 87.32] = 4.392, p = 0.039), with greatest effect within the HIIT group (estimated mean change [95% CI]: -2.64 mmHg, [-4.79 to -0.48], p = 0.017), but no between-group differences were noted (p = 0.17). Both groups also improved cardiorespiratory fitness (F[1, 69] = 34.795, p < 0.001), and TMT A (F[1, 81.51] = 26.871, p < 0.001) and B (F[1, 79.49] = 23.107, p < 0.001). There were, however, no within- or between-group differences in GCF and systolic BP at follow-up. Conclusion: Despite improvements in cardiorespiratory fitness, exercise of high- or moderate-intensity, combined with mind-motor training, did not improve GCF or systolic BP in individuals with hypertension and SCD.